Ergonomic interventions for office workers with musculoskeletal disorders: a systematic review. - Leyshon R; Chalova K; Gerson L; Savtchenko A; Zakrzewski R; Howie A; Shaw L (Work, 2010)
Introduction: Ergonomic interventions designed for office and computer work have become widely available and heavily marketed but there is little evidence to support their use with workers who already have a musculoskeletal disorder (MSD). The purpose of any ergonomic intervention can be to improve worker comfort, safety and/or productivity. The ergonomic research in secondary prevention typically focuses outcomes on improved worker comfort but less if any emphasis has been put on productivity and safety. The purpose of this study was to determine the level and quality of evidence supporting ergonomic interventions to improve the comfort, safety and/or productivity of office workers with symptoms of MSDs. Method: A search of the ergonomic intervention literature based on MSDs of four body areas (low back, upper limb, eye and neck) was employed. The studies underwent two levels of analysis for inclusion in a best-evidence synthesis approach, which included a priori evaluation of specific interventions relative to outcomes of comfort, safety and/or productivity. Results: Twenty-seven out of 202 articles were synthesized based on relevance, quality and significant results. Only 8 articles were determined high quality and no strong levels of evidence were identified. Levels of evidence for specific ergonomic interventions ranged from insufficient to moderate. Generally outcomes were focused mostly on improved comfort of workers. Conclusions: There is still limited quality research that addresses ergonomic interventions designed for secondary prevention. Further high quality studies are needed to support evidence-based ergonomic interventions in practice. For all stakeholders to fully evaluate the usefulness of the ergonomic intervention studies need to attend to outcomes not only of worker comfort but also to productivity and safety.